Pre-Sowing Laser Light Stimulation Increases Yield and Protein and Crude Fat Contents in Soybean - Agnieszka Klimek-Kopyra; Reinhard W. Neugschwandtner; Anna Ślizowska; Dominika Kot; Jan Wincenty Dobrowolski; Zbigniew Pilch; Ewa Dacewicz (Agriculture, 2022)
Pre-sowing laser light stimulation is a method commonly used to increase the productivity of legume species. However, it has not been proved that single-laser light stimulation is a more effective technique for enhancing plant productivity and seed yield quality than using different laser lights in sequence, by which means synergistic relations are produced. A two-year, single-factor field experiment was performed in order to test selected combinations of light stimulation of soybean seeds, the effectiveness of which would be expressed as increased plant yield and improved quality parameters. Pre-sowing light stimulation of soybean seeds was shown to significantly influence the morphological traits of the plants. It significantly increased pod number, pod weight, seed number, and seed weight compared to the control. Coherent laser light stimulation of soybean seeds with a helium–neon laser and with an argon laser increased soybean yields by 30% on average compared to the control. The ratio of the yield from the main shoot to the yield from the lateral branches in this treatment was 40:60, indicating that pre-sowing stimulation of seeds had a significant and positive effect by increasing the yield of the lateral branches relative to the control. Stimulation of seeds (3 × 3 s) with a helium–neon laser significantly increased protein content in soybean seeds, on average by 11% compared to the control. A longer duration of pre-sowing stimulation of seeds (3 × 9 s) resulted in a significant increase in crude fat content in the seeds by an average of 5% compared to the control. The use of physical light stimulation on soybean seeds is a promising solution for increasing soybean yields.